CENTRAL INLAND FISHERIES RESEARCH STATION, CALCUTTA—ITS ORIGIN, ORGANISATION AND FUNCTIONS - Mandapam, Central Marine Fisheries Research Statio (Indian Journal of Fisheries, 2016)
WITH the growing food scarcity in the country both during and after WorldWar IT, fish-farming assumed importance and urgency. There was immediateneed for harnessing all cultivable waters in the country for food production.But as the fundamentals of practical fish-farming as a science andan industry were inadequately known in the country, there was urgent needfor organising fishery research on an all-India basis. The Ministry ofAgriculture of the Government of India therefore sanctioned an interimscheme, which later covered a five-year period, for research on inland fisheryproblems.